PROFIL KEMAMPUAN MAHASISWA PENDIDIKAN BIOLOGI DALAM MEMBUAT LKS BIOLOGI JENJANG SMA - Mayvena Lizora; Pramudiyanti Pramudiyanti; Berti Yolida (Universitas Lampung, 2014)
This study aims to determine the profile of Biology Education, University of Lampung students in preparing worksheets. The research design was simple descriptive with a purposive sampling technique so those 14 students participating in PPL year 2013 which made Biology worksheets taken as subject. Types of data were qualitative such as data conversion worksheets assessment scores, questionnaires, and competency tests. The results showed that students capable enough to make Biology worksheet in terms of format (69.73) and contents (50.45). In terms of format, the composition aspect was categorized enough (49.69), categorized excellent on legibility (92.85) and the categorized good on attractiveness (66.67). In terms of content, categorized either (73.81) in developing appropriate activities and lesson plans, categorized less on elementary Science Process Skills (29.76), and sufficient on advanced Science Process Skills (50,00). Then the students's understanding of the worksheets preparation according to the rules were categorized enough (52.87 and 44.44). Penelitian ini bertujuan untuk mengetahui profil mahasiswa Pendidikan Biologi Universitas Lampung dalam menyusun LKS. Desain penelitian adalah deskriptif sederhana dengan teknik purposive sampling sehingga 14 orang mahasiswa peserta PPL tahun 2013 yang membuat LKS diambil sebagai subjek. Jenis data berupa data kualitatif dari konversi skor penilaian LKS, angket, dan uji kompetensi. Hasil menunjukan mahasiswa berkemampuan cukup dalam membuat LKS Biologi ditinjau dari segi format (69,73) dan isi (50,45). Dari segi format, aspek susunan berkategori cukup (49,69), sangat baik pada keterbacaan (92,85) dan berkategori baik pada kemenarikan (66,67). Dari segi isi, berkategori baik (73,81) dalam menyusun kegiatan yang sesuai dengan KD dan RPP, kurang untuk Keterampilan Proses Sains dasar (29,76), dan cukup untuk Keterampilan Proses Sains lanjut (50,00). Pemahaman mahasiswa mengenai penyusunan LKS sesuai kaidah berkategori cukup (52,87 dan 44,44). Kata kunci : kemampuan, LKS biologi, mahasiswa pendidikan biologi